Knowledge management practice in organizations : the view from inside - De Stricker, Ulla (Advances in knowledge acquisition, transfer, and management (AKATM) book series, 2014)
"This book brings together industry experts to discuss the realities of knowledge management work in organizations, examining the challenges associated with operational knowledge management"--Resumé vydavatele